Positive affect and mortality risk in older adults: A meta‐analysis. Issue 2 (26th April 2016) - Zhang, Yujing; Han, Buxin
Abstract : We performed a meta‐analysis on the relationship between positive affect (PA) and mortality risk in older adults (55 years and older) and reviewed evidence on the Main Effect Model and the Stress‐buffering Model of PA. Four databases (ISI Web of Knowledge, APA PsycNET, PubMed, and Embase) were used to identify potential studies. Three types of effect sizes (ESs), odds ratio, relative risk, and hazard ratio (OR, RR, and HR), were calculated and analyzed within a random effects model. The analysis of the studies in which the effects of other variables were not controlled indicated that older adults with higher levels of positive affect had lower mortality risk (75%, HR = 0.75, 95% confidence interval [CI] = 0.66–0.85) than those with lower positive affect. In studies in which the effects of covariates were controlled, this rate was 85% (HR = 0.85, 95% CI = 0.81–0.89), which was still significant. These results suggest that higher positive affect is associated with lower mortality risk in community‐dwelling older adults, even after controlling for medical, psychological, and social factors. The results point to potential methods of improving longevity, and to achieving healthy aging in older adults.